VD_FINDINFO Jug / 2014 / 66 vom 25. September 2013 - VD Tribunal cantonal (2013)
RESTITUTION DU DÉLAI, CLASSEMENT DE LA PROCÉDURE | 177 al. 2 CP, 310 CPP (CH), 319 al. 1 CPP (CH), 319 CPP (CH), 94 CPP (CH)